Height estimation using 2nd & 3rd metacarpal bone among adult Malay population attending Hospital Universiti Sains Malaysia (HUSM) - Abdul Rasid, Siti Mayzura (2015)
Estimation of individual’s stature is an important parameter in forensic examination. Problems encountered in cases of mass disaster or assaults where the body was dismembered. Many studies have been encountered to determine stature by taking measurement of the long bones. The relationship between specific bone and proportion can be used to help in the process for identification in the absence of complete skeleton from a crime scene. In general, there is a scarcity of literature regarding the estimation of stature (height) among Malaysia population. Up to date there was no published study regarding height estimation among Malay population in Kelantan using metacarpal bone parameters. The regression formulae are population specific. Therefore, the aim of the present study was to set a general formula of stature estimation for both adult males and females using anthropometrical measurements of second and third metacarpal bones using AP hand radiograph among Malay adults attending Hospital Universiti Sains Malaysia. Objectives: The general objective of this study was to estimate stature from the morphology of left hand radiograph among adult Malay population attending Hospital Universiti Sains Malaysia. Patients and methods: This was a cross-sectional study among adult Malay Kelantan population attended HUSM for posterior anterior (PA) view radiograph of left hand. A total of 124 subjects with age ranged from 19 to 60 years old were included. The length and width of the normal 2nd and 3rd metacarpal bones together with their heights were measured.Data entry and analysis were performed usingStatistical Package for Social Sciences (SPSS version 22) software programme. The descriptive demographic data were measured using independent t-test. The correlation between stature and parameters of metacarpal bones were performed using Pearson Correlation. The prediction of stature from the parameters of metacarpal bone were using simple linear regression and multiple (stepwise) regression analysis. Results: Statistical analysis revealed that parameters formale subjects were higher than the female subjects (p <0.001). There was significant correlation between all the parameters of second and third metacarpal bones in female subjects (p value <0.001 and p value 0.05). For male subjects, significant correlation noted between stature and the length of second and third metacarpal bone (p value <0.001). Using simple linear regression analysis, the standard error of estimate (SEE) ranged from ±3.94cm to ±4.97cm for males and ±3.92cm to ±4.55cm for females. From the simple linear regression analysis, four regression equations were established for each gender. The multiple linear regression analysis revealed smallest SEE from the second metacarpal bone length for male (SEE ±3.94). For female subject the multiple linear regression analysis revealed smallest SEE revealed from the second metacarpal bone length and width (SEE ±3.78 cm). Therefore, one multiple regression equation was established for each gender using the second metacarpal bone parameter. Conclusion: It was concluded that stature can be determined successfully using 2nd metacarpal bone parameters which were the length for male and both length and width for female among adult Malay population in Kelantan.